Berkeley's idealism : a critical examination - Dicker, Georges, 1942- (New York ; Oxford : Oxford University Press, 2011)
Using the tools of contemporary analytic philosophy, Georges Dicker here examines both the destructive and the constructive sides of Berkeley's thought, against the background of the mainstream views that he rejected.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Berkeley, George, -- 1685-1753.; Idealism; Idea (Philosophy); Metaphysics